Impact of consumption of the human milk oligosaccharides 2′-FL and LNnT on reduction of risk of allergic sensitisation - Sébastien Holvoet; Francis Foata; Sophie Nutten; Ellen Ní Cléirigh; Maya Shevlyakova; Cheong Kwong Chung; Gregory Lefevre; Norbert Sprenger; Tristan Bourdeau; Dominique Donnicola; Mario Noti; Severine Combremont; et al. (Food and Agricultural Immunology)
Human Milk Oligosaccharides (HMOs) have been proposed to be instrumental in building immune competence. To explore the role of HMOs in allergy prevention, twenty-one HMOs were quantified in breast milk samples and associated with sensitisation in infants. 2′-fucosyllactose (2′-FL) levels were positively associated with an increased risk of sensitisation, atopic dermatitis and recurrent skin rash. Interestingly, 2′-FL levels, ranging from 1.35 to 1.95 g/L, were associated with a higher prevalence of non-allergic and non-sensitised infants. The role of 2′-FL and lacto-N-neotetraose (LNnT) was further investigated in allergic sensitisation models in vivo. Oral administration of HMOs decreased allergic sensitisation. This was associated with gut microbiota and short-chain fatty acid (SCFA) production changes. Aligned with the clinical associations, the decreased sensitisation was not observed with lower and higher tested doses of the HMOs supporting a U-shape association between 2′-FL and LNnT levels and allergic sensitisation risk reduction in humans and mice.Trial registration: ClinicalTrials.gov identifier: NCT02550236.